2004
DOI: 10.1038/ncb1120
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Arf-like GTPase Arl3p to the Golgi requires N-terminal acetylation and the membrane protein Sys1p

Abstract: The GTPase Arl3p is required to recruit a second GTPase, Arl1p, to the Golgi in Saccharomyces cerevisiae. Arl1p binds to the GRIP domain, which is present in a number of long coiled-coil proteins or 'golgins'. Here we show that Arl3p is not myristoylated like most members of the Arf family, but is instead amino-terminally acetylated by the NatC complex. Targeting of Arl3p also requires a Golgi membrane protein Sys1p. The human homologues of Arl3p (Arf-related protein 1 (ARFRP1)) and Sys1p (hSys1) can be isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
239
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(254 citation statements)
references
References 47 publications
13
239
1
1
Order By: Relevance
“…The maturation process may effect this change in fusogenic potential by the recruitment or loss of specific components of the fusion machinery. Interestingly, other small four-transmembrane domain proteins, including Yip1p and Sys1p, are required for the recruitment of small GTPases to specific compartments (Yang et al, 1998;Behnia et al, 2004;Setty et al, 2004). Although we were unable to detect a physical association between the Vps55/68 complex and the endosomal Rab GTPase Vps21p, the presence of these proteins in the same phenotypic cluster suggests the Vps55/68 complex may interact transiently with Vps21p to fulfill a specific step in endosome maturation.…”
Section: The Vps55/68 Complex Is Required For Two Transport Steps Outcontrasting
confidence: 38%
“…The maturation process may effect this change in fusogenic potential by the recruitment or loss of specific components of the fusion machinery. Interestingly, other small four-transmembrane domain proteins, including Yip1p and Sys1p, are required for the recruitment of small GTPases to specific compartments (Yang et al, 1998;Behnia et al, 2004;Setty et al, 2004). Although we were unable to detect a physical association between the Vps55/68 complex and the endosomal Rab GTPase Vps21p, the presence of these proteins in the same phenotypic cluster suggests the Vps55/68 complex may interact transiently with Vps21p to fulfill a specific step in endosome maturation.…”
Section: The Vps55/68 Complex Is Required For Two Transport Steps Outcontrasting
confidence: 38%
“…10 While the functional implications of this modification are not fully understood, a number of roles have been observed including enhancing protein-protein [11][12][13] and protein-membrane interactions 14,15 both of which are relevant to AS. Acetylation removes the N-terminal charge, making this region of the protein more hydrophobic.…”
Section: Resultsmentioning
confidence: 99%
“…This altered complex still displays 60 -80% of the wild type NatA activity but appears to be lethal within few days after birth. Although NAA is associated to specific roles for several protein groups such as cytoskeleton protein binding (30 -32) or protein targeting to a given compartment (33)(34)(35), its intrinsic function has remained elusive for the large majority of the proteins. Nevertheless, it was suggested that NAA is an important factor influencing protein half-life either globally or in some protein groups (4, 36 -38).…”
mentioning
confidence: 99%